Determination of Performance in Sharia Banks Based on Islamic Corporate Governance and Investment Account Holders - Laely Aghe Africa (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study aims to analyze the effect of ICG (Islamic Corporate Governance) and IAH (Investment Account Holders) on the performance of Sharia banks in Indonesia as proxied by Mudharabah financing, Musyarakah financing, ROA (Return on Assets), and ROE (Return on Equity). 110 data used in this study are in the form of financial statements of Sharia banks in Indonesia for the period of 2010 – 2019 Design/methodology/approach: This study uses quantitative method and multiple regression analysis with SPSS Version 23 Findings: The results of this study show that ICG and IAH have an effect on Mudharabah financing, Musyarakah financing, ROA, and ROE Research limitations/implications: This study is expected to serve as a guideline for banking management in making policies on company performance, as measured by Mudharabah financing, Musyarakah financing, ROA and ROE, and corporate governance, as measured by ICG, so that Islamic banking companies have their own guidelines in determining policies related to banking operations that are adjusted to the decisions of the Financial Services Authority of the Republic of Indonesia (OJK). Practical implications: State your implication here. Originality/value: originality Paper type: Research paper